A review on the role of fatty acids in colorectal cancer progression - Malvina Hoxha; Bruno Zappacosta (Frontiers Media S.A., 2022)
Colorectal cancer (CRC) is the third leading cause of mortality in cancer patients. The role of fatty acids (FA) and their metabolism in cancer, particularly in CRC raises a growing interest. In particular, dysregulation of synthesis, desaturation, elongation, and mitochondrial oxidation of fatty acids are involved. Here we review the current evidence on the link between cancer, in particular CRC, and fatty acids metabolism, not only to provide insight on its pathogenesis, but also on the development of novel biomarkers and innovative pharmacological therapies that are based on FAs dependency of cancer cells.